KETERLIBATAN MASYARAKAT DALAM PENGELOLAAN OBJEK WISATA PERMANDIAN WAKUMORO DI KABUPATEN MUNA - Tasbin Salam; Grystin Djein Sumilat; Abdul Rasyid Umaternate (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2021)
The purpose of this study was to determine community involvement in the management of the Wakumoro bathing tourism object in Wakumoro Village, Parigi District, Muna Regency. This study uses a qualitative approach. Data were obtained by using observation, interviews, and documentation, while data analysis used data reduction procedures, data display, and concluding. The results showed that the community was involved in planning activities for the management of Wakumoro tourism objects. The form of community involvement is attending planning invitations and being involved in decision-making. The community is involved in the implementation of Wakumoro tourism object management activities. The form of community involvement during implementation is being involved in the procurement of tourist facilities which include participating in community service, opening food stalls, and as a service provider such as motorcycle taxis and swimming aids. The community is involved in evaluating the management of the Wakumoro bathing tourist attraction in Wakumoro Village, Parigi District, Muna Regency. The form of community involvement during the evaluation is attending the invitation to evaluation activities and being involved in decision making. Factors that influence community involvement in the management of Wakumoro tourism objects are work or busyness factors in meeting the needs of daily life and the lack of community knowledge about tourism so that in every meeting from planning, implementation to evaluation, they do not provide ideas. Overall work, knowledge, and level of education are factors that influence community involvement in the management of Wakumoro bathing tourism objects.